A mathematical model of heat transfer during tomato peeling using selected electric infrared emitters. (October 2019) - Vidyarthi, Sriram K.; El Mashad, Hamed M.; Khir, Ragab; Upadhyaya, Shrinivasa K.; Singh, Samrendra K.; Zhang, Ruihong; Tiwari, Rakhee; Pan, Zhongli
Abstract : A two-dimensional mathematical model of heat transfer was developed for heat transfer during the infrared (IR) peeling of tomato. The model was used to predict the temperatures of tomato heated using selected electric IR emitters having different characteristics. The IR heating process was hypothesized as a mathematically gray-diffuse radiation problem based on the enclosure theory. The heat transfer model was solved in COMSOL using a finite element scheme to predict the temperature of tomato during different heating times. The model was validated by comparing the predicted and measured temperatures of tomato surface that were presented in our accompanying study (Vidyarthi et al., 2019). The predicted temperatures agreed well with the experimental data (R 2 > 0.99). Simulation results indicated that IR heating for 25 s induced a dramatic temperature increase (>100 °C) on the tomato surface layers; limited to a maximum of 0.66 mm underneath the surface. There was no change in the temperature of tomato center (<28 °C). The rapid increase of tomato surface temperature and insignificant rise in interior temperature indicated a meager penetration capacity of IR radiation, causing insubstantial damage to tomato flesh integrity, and consequently preserving the nutritional quality of peeled product. This study provides designing parameters of an efficient IR tomato peeling technology, ensuring a high peeling performance and product quality. Highlights: A two-dimensional heat transfer model was developed for the infrared (IR) peeling of tomato. The predicted and experimental surface temperatures of tomato agreed well. Tomato surface layers experienced a dramatic increase of temperature. Tomato interior showed insignificant rise in temperature. Indicated a higher integrity of tomato flesh and a better quality of peeled product.